A review from experimental trials on detoxification of aflatoxin in poultry feed - Halis Oguz (Eurasian Journal of Veterinary Sciences)
In this meta-analytic review, in vivo experimental trials on inactivation of aflatoxins by using adsorbents and biological products as a feed additive in poultry feed were briefly summarized after given the general information about this subject. For this purpose, 135 study performed in 33 different countries were examined and classified according to countries and their results were presented. The aim of this review is to present the results of the experiments to the producers and scientists and to provide a total evaluation possibility to them on the basis of the countries. The best way for the producers and scientists to assess the performance of preventive efficacy of used feed additive is to evaluate the results "as total" in terms of performance, bi-ochemical-hematological, immunological and gross and his-topathologic parameters by comparing the aflatoxin groups with aflatoxin plus feed additive groups. The producers and scientists can reach to the total experiment for assessing preventive efficacy and practical usability of feed additives by following the titles of articles, associate authors and/or materials and methods of articles.